STUDENTS’ PERCEPTION AND THE EFFECTIVENESS OF CORPORATE SOCIAL RESPONSIBILITY AMONG UiTM SARAWAK BRANCH - Ahmad Shahir Abd Aziz; Rumaizah binti Che Md Nor; Siti Sahmsiah Sahmat (Jurnal Penyelidikan Sains Sosial, 2020)
Corporate Social Responsibility (CSR) is now captured the global interest in most of institution, public as well as private sectors. Hence, higher learning education has taken this opportunity to contribute into social activities and build strategies to strengthen their relationship with social through their education programs. The aims of this paper are to determine if perceptions of students on the CSR programs run by the university is differ according to sociodemographic variable such as gender and academic level background and to evaluate the effectiveness of the programs towards the student’s attitude, team work and leaderships. Data collected from 92 students from various courses in UITM Sarawak Branch and processed by using SPSS software. The result suggests that students have high perception towards CSR Program. It means that they are very like joining the program and feel that the program gave them a lot of benefits and experience. Finding of this study also shows that the sociodemographic does not influence students’ perceptions towards CSR program. This study reveals that CSR programs gives a high effectiveness towards students’ attitude, team work and leadership. These programs have teach them to have a good manner, work in a team and how to be a good leader successfully. Correlation analysis also has been done for this study and found that there is a significant moderate positive relationship between perception and effectiveness of CSR programs among UiTM students. It means that if student highly agreed with CSR programs, the programs also will be more effective.